PENGARUH PEMBERIAN NEURODYNAMIC MOBILIZATION (NDM) MELALUI DIGITAL TERHADAP NYERI CARPAL TUNNEL SYNDROME (CTS) PADA OJEK ONLINE - Syhakira Rahmadhani Husein Nasution; Agus Riyanto; Suci Muqodimatul Jannah (Journal of Innovation Research and Knowledge, 2026)
Background: Carpal Tunnel Syndrome (CTS) is a common compression neuropathy, frequently experienced by workers performing repetitive movements, including online motorcycle taxi drivers. Pain and functional impairments caused by CTS can be managed through physiotherapy interventions. This study aims to investigate the effect of Neurodynamic Mobilization (NMD) delivered through digital media on reducing pain levels in CTS patients among online motorcycle taxi drivers. This study employed a pre-test and post-test design on a single intervention group. A total of 20 respondents (14 males, 6 females) diagnosed with CTS and working as online motorcycle taxi drivers were selected using a non-probability convenience sampling method according to inclusion criteria. The intervention consisted of NDM techniques: Sliding and Tensioning of the Median Nerve. Exercises were delivered digitally using the Physitrack application for the researcher and PhysiApp for the respondents over a 2 week period, with a frequency of five sessions per week (2 sets of 10 repetitions per session). Pain levels were measured before (pre-test) and after (post-test) the intervention’s effect. The results showed that the average pain level before the intervention (Pre-VAS) was 6.25. After the digital NDM intervention, pain levels decreased significantly (Post-VAS). The Wilcoxon test yielded a significance value (P-value) of 0.000 (P<0.05), indicating a highly significant effect of NDM on reducing CTS-related pain. Delivering NDM via digital media is effective in reducing pain levels in online motorcycle taxi drivers with CTS. NDM can serve as a pratical and effective intervention option for managing CTS pain in populations engaged in digital-based workrecommended as physiotherapy interventions for NPBNS in the elderly, taking into account patient comfort and clinical needs. Further research with larger samples and longer intervention durations is needed to confirm these findings.